2011
DOI: 10.3390/su3050743
|View full text |Cite
|
Sign up to set email alerts
|

A Meta Analysis on Farm-Level Costs and Benefits of GM Crops

Abstract: This paper reviews the evidence on the socio-economic impacts of GM crops and analyzes whether there are patterns across space and time. To this end, we investigate the effect of GM crops on farm-level costs and benefits using global data from more than one decade of field trials and surveys. More specifically, we analyze the effects of GM-crops on crop yields, seed costs, pesticide costs, and management and labor costs and finally gross margins. Based on collected data from studies on Bt cotton and Bt maize, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 37 publications
4
74
0
Order By: Relevance
“…Overall, the crops are bound to be the most advantageous for farmers economically. Higher economic performance as a result of adopting GM crops was documented in previous reviews or in meta-analyses around the world [32].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Overall, the crops are bound to be the most advantageous for farmers economically. Higher economic performance as a result of adopting GM crops was documented in previous reviews or in meta-analyses around the world [32].…”
Section: Discussionmentioning
confidence: 80%
“…Although reflections by the advocates of GM crops on the potential of these crops might attract more attention by providing solutions to the current problems of conventional agriculture [31], the critics portray a troublesome outlook on the negative environmental, economic, and social impacts of GM crops. Finger et al (2011) [32] believes that the contradictions arising on both sides of the debate (pro and con-GM crops) point to individual studies. They found that it was necessary to review the impacts that have been observed in different countries in order to create a comprehensive global prospect.…”
Section: Gm Cropsmentioning
confidence: 99%
“…However, a significant number of studies discussed yield and farm finances without own bottom-up data (52/83 studies). This meant that existing empirical data on yield and farm finances were repeated in many studies (e.g., [14,[56][57][58][59]). This could give the impression that claims of increased yields and profits have a more substantial empirical foundation than is actually the case.…”
Section: How Are Different Social Impacts Addressed?mentioning
confidence: 99%
“…Agricultural economists looking across several countries in the global South have found "Bt cotton's impacts are 'inconclusive'" to date (Smale et al 2007). However, recent research says that Bt cotton is most impressive in a context where previous loss of the crop due to pests was extensive; alternatively, where there is less dramatic crop loss, the impact of Bt cotton is less significant (Finger et al 2011). A reliance on increased yield and profitability data as the overriding justification for Bt cottonwhich is not uncommon among those advocating for its use (as evidenced in the sheer mass of industry, State, and economic-development groups yield studies 16 ) -may actually overshadow other potential benefits for farmers in those locations where crop loss due to bollworm is less extensive.…”
Section: ____________________________________________________________mentioning
confidence: 99%